2018
DOI: 10.1016/j.kint.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of the adipokine zinc-alpha2-glycoprotein (ZAG) predict mortality in hemodialysis patients

Abstract: Wasting has been associated with increased cardiovascular and all-cause mortality in chronic kidney disease (CKD). We investigated whether serum zinc-alpha2-glycoprotein (ZAG), a potent cachectic and lipid-mobilizing factor that is increased in patients with CKD, predicts clinical outcomes in patients on chronic hemodialysis. We quantified serum ZAG at baseline in a prospective cohort of 252 patients undergoing maintenance hemodialysis. Serum ZAG concentrations were inversely associated with serum albumin, cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
1
12
1
Order By: Relevance
“…Zinc-alpha-2-glycoperotein (ZAG) is a 41-kDa glycoprotein synthesized by epithelial cells and adipocytes and plays a role in lipid metabolism, cell cycling and cancer progression. Serum ZAG levels has been reported as a biomarker of renal injury and can predict mortality in hemodialysis patients 5 . However, these changes in serum ZAG levels have not been reported in LC patients with ascites.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc-alpha-2-glycoperotein (ZAG) is a 41-kDa glycoprotein synthesized by epithelial cells and adipocytes and plays a role in lipid metabolism, cell cycling and cancer progression. Serum ZAG levels has been reported as a biomarker of renal injury and can predict mortality in hemodialysis patients 5 . However, these changes in serum ZAG levels have not been reported in LC patients with ascites.…”
Section: Introductionmentioning
confidence: 99%
“…As an adipokine, ZAG is mainly secreted by subcutaneous and visceral adipocytes and is involved in stimulating adipocytes to induce lipid degradation (Yang et al, 2013). It has been reported that ZAG is related to the markers of insulin resistance or obesity and may play a role in the pathogenesis of insulin resistance (IR) (Bouchara et al, 2018). ZAG index can be served as an indicator to identify IR (Qu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although kidney transplantation offers clear survival benefits compared to dialysis, CVD remains one of the leading causes of premature death after transplantation ( 22 ). As AZGP1 has been identified as a potential modifier of CVD ( 14 16 ), we first assessed serum AZGP1 changes after kidney transplantation over a period of 2 years. We found a continuous decline in AZGP1, which paralleled eGFR improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there is a discrepancy in reported effects of AZGP1 on CVD between patients with and without chronic kidney disease (CKD). While higher AZGP1 levels were associated with reduced incidence of coronary heart disease and atherosclerosis in non-CKD patients (14,15), higher AZGP1 levels were shown to correlate positively with CVD in ESRD patients (16). It is therefore interesting, that so far, AZGP1 has not been investigated in the context of kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%